2007
DOI: 10.1111/j.1365-2702.2006.01759.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the facets of continence care: a continence survey of care homes for older people in Birmingham

Abstract: While there is an existing body of knowledge relating to continence prevalence and management in nursing homes this research base is lacking for residential care settings. This survey addresses this imbalance by combining information from both settings. This paper also provides an insight into the components that have an impact upon continence promotion, prevention and management. By establishing a picture of current practice an indication of areas for improvement can be exposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 20 publications
2
40
0
Order By: Relevance
“…Regarding sub‐types, the most frequent were functional UI (impossibility of reaching the toilet facilities) due to physical or cognitive impairments, followed by urgency and stress UI. According to the international scientific literature, the frequency of functional UI observed herein was higher, with lower rates for stress and urgency UI, which can be attributed to a high level of physical inactivity, mobility restrictions, functional dependency, and dementia . Furthermore, it was observed that not‐for‐profit NH have a low number of caregivers, which limits the stimuli and assistance that disabled residents should receive to access the toilet.…”
Section: Discussionmentioning
confidence: 66%
“…Regarding sub‐types, the most frequent were functional UI (impossibility of reaching the toilet facilities) due to physical or cognitive impairments, followed by urgency and stress UI. According to the international scientific literature, the frequency of functional UI observed herein was higher, with lower rates for stress and urgency UI, which can be attributed to a high level of physical inactivity, mobility restrictions, functional dependency, and dementia . Furthermore, it was observed that not‐for‐profit NH have a low number of caregivers, which limits the stimuli and assistance that disabled residents should receive to access the toilet.…”
Section: Discussionmentioning
confidence: 66%
“…This is consistent with the results of Rodriguez et al . () where 50% of the nursing homes used absorbent products to manage incontinence. Wagg et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nursing home residents and nursing home institutions worldwide have gone through a great change during the past decades, with increasingly frail residents with multiple comorbidities. However, many fecal incontinence studies are from the 80s and 90s [4-7,9,10,14-16], but there are some studies from the past decade [3,8,17,18]. Previous studies have demonstrated the complexity of fecal incontinence among frail older residents.…”
Section: Introductionmentioning
confidence: 99%